Visualisasi Kualitas Penyebaran Informasi Gempa Bumi di Indonesia Menggunakan Twitter - Mira Chandra Kirana; Nanda Putra Perkasa; Muhammad Zainuddin Lubis; Maidel Fani (Journal of Applied Informatics and Computing, 2019)
Indonesia is one country with a high level of natural disasters, such as earthquakes, so the dissemination of information about early warning is very important.. Social media Twitter became one of the places of broadcasting information about earthquake disaster early instruction in Indonesia through BMKG account. However, the quality of information from Twitter's social media is unknown, therefore visualization is made to analyze the quality of information with Twitter social media. This research is done in three stages: retrieving, preprocessing and visualization. Retrieval process to capture BMKG Tweet account data on Twitter. Preprocessing phase of work to get the results of the analysis of the quality of earthquake information. After that done data processing timeliness, relevance, completeness of data along with the accuracy of data created based on graphical visualization information.